PENGARUH GAJI DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT PEGADAIAN SYARIAH CABANG KEUTAPANG ACEH BESAR - Syarifah Mauli Masyitah; Banta Karollah; Syafira Yunidar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2023)
This study aims to determine the effect of salary and job experience toward employee performance at PT Pegadaian Syariah branch Keutapang Aceh Besar, either partially or simultaneously. There were 37 respondents as samples in this study. The result of study based on simultaneous test showed that the variable of salary and job experience have a significant effect on employee performance at PT Pegadaian Syariah branch Keutapang Aceh Besar. The partial test also showed that both variable of salary and job experience significantly affect the employee performance at PT Pegadaian Syariah branch Keutapang Aceh Besar. This study showed that salary significantly affects employee performance with a result of t value (3,667) is higher than t table (2,032) as well as job experience that has significant effect which is t value (3,172) is larger than t table (2,032). In addition, salary and job experience simultaneously affect employee performance at PT Pegadaian Syariah branch Keutapang Aceh Besar which is F value (2,987) is higher than F table (3,276).